Microencapsulation techniques: a proposal for microencapsulated probiotics. - Martín Villena, MJ; Morales Hernández, ME; Gallardo Lara, V; Ruiz Martínez, MA (Ars Pharmaceutica (Internet), 2009)
The main problem when probiotics are used is the low resistance of these to different environmental and technological conditions. The microencapsulation techniques are a good method in order to protect the probiotics, Nevertheless not all techniques of microencapsulation are suitable for probiotics. In this paper, we propose the internal gelification which allows us to obtain a suitable particle size and the survival of the microorganisms.